PENGEMBANGAN TEKNOLOGI BET NON KARBON DAN KARBON DALAM PERMAINAN TENIS MEJA - Rivan Saghita Pratama; Indra Ramadhan; Syahnata Deningtyas Putri; Fatimah Nurul Laksmi (STKIP Subang, 2025)
This research aims to examine the development of non-carbon and carbon bettechnology in table tennis games. Table tennis as a sport that relies on speed,accuracy, and strategy has undergone significant evolution in the development ofequipment, especially the bet which is the main instrument of the player. Themethod used in this research is a comprehensive literature study by analyzingfindings from 70 reliable references, consisting of 40 international sources and 30national sources, regarding material developments, manufacturing processes, andthe impact of bet technology on athlete performance. The results show that thedevelopment of non-carbon bet has diversified in the use of wood materials withinnovations in lamination techniques, while carbon bet has revolutionized with theapplication of nanotechnology and advanced composite fibers. A comparison ofthe two technologies shows that carbon bet offers advantages in terms of strength,durability and high-level performance, while non-carbon bet is still relevant forbeginner players and certain styles of play. Recent innovations have led to theintegration of sustainable materials and hybrid technologies that optimizeperformance while taking into account environmental aspects. In conclusion, theselection of the optimal bet technology depends on the players characteristics,playing technique, and level of competition, and future development trends will beoriented towards personalization, environmental friendliness, and materialefficiency.